2022
DOI: 10.3390/ijerph192316169
|View full text |Cite
|
Sign up to set email alerts
|

A Future Perspective on Waste Management of Lithium-Ion Batteries for Electric Vehicles in Lao PDR: Current Status and Challenges

Abstract: Lithium-ion batteries (LIBs) have become a hot topic worldwide because they are not only the best alternative for energy storage systems but also have the potential for developing electric vehicles (EVs) that support greenhouse gas (GHG) emissions reduction and pollution prevention in the transport sector. However, the recent increase in EVs has brought about a rise in demand for LIBs, resulting in a substantial number of used LIBs. The end-of-life (EoL) of batteries is related to issues including, for example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…This concern stems from the potential environmental risks associated with improper disposal methods, such as landfilling and incineration [74]. These risks are particularly relevant for SSBs, which are gaining prominence due to their high energy density and potential applications in electric vehicles and grid-scale energy storage [78]. SSBs offer advantages such as higher energy density, longer lifespan, and improved safety compared to traditional lithium-ion batteries.…”
Section: Environmental Risks Associated With Landfills and Incinerationmentioning
confidence: 99%
See 1 more Smart Citation
“…This concern stems from the potential environmental risks associated with improper disposal methods, such as landfilling and incineration [74]. These risks are particularly relevant for SSBs, which are gaining prominence due to their high energy density and potential applications in electric vehicles and grid-scale energy storage [78]. SSBs offer advantages such as higher energy density, longer lifespan, and improved safety compared to traditional lithium-ion batteries.…”
Section: Environmental Risks Associated With Landfills and Incinerationmentioning
confidence: 99%
“…In addition to the direct environmental risks, landfilling and incineration of SSBs also lead to resource wastage [81]. These batteries contain valuable and scarce materials, such as lithium, cobalt, nickel, and manganese [78]. Disposing of SSBs in landfills or incinerating them means losing the opportunity to recover and reuse these valuable resources [82].…”
Section: Environmental Risks Associated With Landfills and Incinerationmentioning
confidence: 99%
“…From a consumer aspect, Boguslavsky, Sharov and Sharova find that the use of green energy may not be eco-friendly, mainly due to the environmental pollution caused by the storage of electrical energy usually with the help of lithium compounds [ 27 ]. Moreover, the increase in demand for lithium batteries in pure EVs triggers the battery end-of-life problem [ 28 ]. There is a lack of relevant international standards to make uniform regulations on the management of used lithium batteries, while the extension of the manufacturers’ responsibility increases the after-sales cost [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In (35) they concluded that only 1% to 3% of total passenger cars are electric today In (36) authors confirm that a customer willing to use an electric vehicle (EV) needs the vehicle to have shorter charging durations, lesser maintenance, and a cheaper cost of operation. (37) This review examines the latest technological advancements in Li-ion batteries for electric vehicle applications. The authors discuss the challenges and opportunities to improve the performance, safety, and durability of batteries.…”
Section: Operatingmentioning
confidence: 99%